A Study on Direct Corrective Feedback in Improving Students' Writing Performance and Motivation at MTs YP KH Syamsuddin Ponorogo - Novika Agustiningsih; Fenty Andriani (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2021)
This research is aimed to foster students’ motivation in improving writing performance by implementing direct corrective feedback. Direct error correction identifies both the error and the target form. Providing corrective feedback is an essential part of language learning because it influences students’ learning and achievement. Feedback helps both teachers and students to meet their goals in teaching and learning. Feedback and motivation are two perceptions which control the students’ English as foreign language improvement and progress in learning. This research applied a descriptive qualitative research method. Data gathered through observation, interview, questionnaire, and relevant documents. The research was conducted in the seventh C grade of MTs YP KH Syamsuddin Ponorogo. Thirty five students participated in this research by filling out a questionnaire, and interviewed to obtain more information related to their responses to the questionnaire. The finding of this research indicates that the implementation of direct corrective feedback in improving students’ writing performance and motivation in writing teaching learning process was divided into two ways: oral and written. There was also such improvement on students’ motivation. The students’ responses toward the implementation of direct corrective feedback in improving the students’ writing performance were positive because it made them feel comfort in the learning process.